2016
DOI: 10.1177/0312896216640862
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the habit of self-service technology usage

Abstract: Prior self-service technology (SST) studies focus primarily on the initial adoption and its drivers. However, the long-term viability and success of an SST depend on regular and frequent usage. Therefore, this study draws on social psychology and information system/information technology literature to investigate the habit of SST usage and its driving forces. Using panel data pertaining to 626 Australian customers who used a supermarket self-checkout machine over 12 weeks, the results reveal a strong carryover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…This suggests that inherent thinking styles or abstract perceptions of technology may not sufficiently explain the choice between traditional service and SST. Accordingly, situational factors like perceived or experienced waiting time (Djelassi, Diallo, & Zielke, 2018;Gelderman et al, 2011) and automatic behaviours like habits (Wang et al, 2013(Wang et al, , 2017 have been found to significantly shape SST use behaviour. Wang et al (2013) find that customer's decision to continue SCO usage is initially rationally driven, then emotionally driven, and finally becomes habitual.…”
Section: Setting the Scene: The Selection Of Self-checkout Over Traditional Checkoutmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that inherent thinking styles or abstract perceptions of technology may not sufficiently explain the choice between traditional service and SST. Accordingly, situational factors like perceived or experienced waiting time (Djelassi, Diallo, & Zielke, 2018;Gelderman et al, 2011) and automatic behaviours like habits (Wang et al, 2013(Wang et al, , 2017 have been found to significantly shape SST use behaviour. Wang et al (2013) find that customer's decision to continue SCO usage is initially rationally driven, then emotionally driven, and finally becomes habitual.…”
Section: Setting the Scene: The Selection Of Self-checkout Over Traditional Checkoutmentioning
confidence: 99%
“…This suggests that attitude and intention alone do not always predict actual behaviour exhaustively. Even though the link is strong in the initial usage phase, the significance of deliberate attitudes and intentions weakens during the habit formation and thus they are inadequate to explain automatic, habit-driven behaviour (Limayem, Hirt, & Cheung, 2007;Wang et al, 2013Wang et al, , 2017. However, for a habit to form, customers need to adopt and use the technology first.…”
Section: Setting the Scene: The Selection Of Self-checkout Over Traditional Checkoutmentioning
confidence: 99%
“…The prior literature suggests the effect of experience in the adoption of SSTs (Demoulin and Djelassi [31]. Wang, Harris [97] revealed prior habit as the most crucial determinant on the use of SSTs whereas Castro, Atkinson [10] identified that in a circumstance where the technology is new previous experience in using SSTs is crucial. Furthermore, individual differences [13] and consumer context [9] including the past experiences they had have also been recognized as important in the acceptance of SSTs.…”
Section: The Effect Of Past Experience On Customer Value Co-creation/codestruction In Sstsmentioning
confidence: 99%
“…Habit and experience of similar technology have also been found as significant in SST adoption [41]. Wang, Harris [47] identify prior habit as the most powerful precursor on SST usage, while Castro, Atkinson [8] argue that previous experience in using SSTs is crucial when the technology is new. Influences of personal control on the adoption of self-service technologies was recognized by Lee and Allaway [48].…”
Section: Customer Choice Of Ssts and Theoretical Foundations To Understand The Acceptancementioning
confidence: 99%